Incorporating combined cycle gas turbine flexibility constraints and additional costs into the EPLANopt model: The Italian case study. (1st October 2018) - Prina, Matteo Giacomo; Fanali, Lorenzo; Manzolini, Giampaolo; Moser, David; Sparber, Wolfram
Abstract: The planning of an energy system with high penetration of renewables is increasing in complexity as only an effective implementation can allow the tackling of environmental and energy security issues. The aim of this study is to present the integration of combined cycle gas turbine cycling costs in EPLANopt, a simulation software consisting of EnergyPLAN coupled to a Multi-Objective Evolutionary Algorithm. The model is then applied to the Italian energy system which is characterized by a very high capacity and electricity production from combined cycle gas turbine systems. The proposed approach established a first step in the direction of modelling their role for load modulation accounting for technical constraints and additional costs related to start-up and partial load condition. Results show the importance of considering cycling costs of combined cycle gas turbine system within energy system modelling as the nature of these costs at the increasing of intermittent renewable generation can reach peaks of 33.5 €/MWh. Additionally, the inclusion of CCGT cycling costs in high penetration non programmable renewable energy sources scenarios opens up favorable business models for other load modulation strategies (e.g. electric batteries). Highlights: A method to integrate combined cycle cycling costs in energy system modelling. Multi-objective optimization model EPLANopt is chosen as energy system model. The method is applied to the Italian case study towards high renewables penetration. Focus is on the impact of cycling on the future best mix of technologies. Results showed cycling costs are not negligible and can reach peaks of 33.5 €/MWh.